Best Answer

I x=5 and y=2, then (5x5)=25 plus (9x2)=18. 25+18=43

Q: If x equals 5 and y equals 2 then 5x plus 9y equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

8x-7 plus 2x equals 6 plus 5x plus 2?

Here is the work for that problem: 5x+ 2=12 5x= 12-2 5x=10 x= 2

3x + 2 + 2x = 7; 3x + 2x = 5x, so 5x + 2 = 7; 7-2=5, so 5x=5. 5x divided by 5 and 5 divided by 5 equals 1, so x equals 1.

(4, -2)

Related questions

x = 2, y = 1

5x-4y+9y+x-9+7 = 5x + x - 4y + 9y - 9 + 7 = 6x + 5y - 2 ■

If: 5x-9y = 7 and 7y-3x = -5 Then: x = 1/2 or 0.5 and y = -1/2 or -0.5

5x + 9y = 06x + 6y = 2 use substitution method5x + 9y = 0y = -5x/96x + 6y = 2 substitute y with -5x/96x + 6(-5x/9) = 26x - 30x/9 = 2 multiply by 9 to both sides54x - 30x = 1824x = 18x = 24/18 = 4/3y = -5x/9 = (-5/9)x substitute x with 4/3y = (-5/9)(4/3) = -20/27Thus the solution is x = 4/3 and y = -20/27.

1. 6x - 5y = 22 2. 5x - 9y = -1 1 times 5: 30x - 25y = 110 2 times 6: 30x - 54y = -6 Subtract : 29y = 116, so y = 4 and x therefore = 7

5x(6x + 9y + 2)

It is an algebraic expression that can be simplified to: 5x+9y+5

8x-7 plus 2x equals 6 plus 5x plus 2?

(1, -1)

f(x)=5x+2

7x + 3y = 14 5x + 9y = 10 __________ (subtract bottom from top) 2x -6y = 4, therefore 2x = 4 + 6y, therefore x = 2 + 3y Insert x = 2 + 3y into the original equation and calculate 7(2 + 3y) +3y = 14 14 + 21y +3y = 14 24y = 0 y = 0 If y= 0, then x = 2 FINAL ANSWER!

-3x+9y = 6 9y = 3x+6 y = 1/3x+2/3